2020
DOI: 10.1186/s13023-020-01399-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase II, open-label, extension study of long-term patisiran treatment in patients with hereditary transthyretin-mediated (hATTR) amyloidosis

Abstract: Background: Patisiran, an RNA interference therapeutic, has demonstrated robust reduction of wild-type and mutant transthyretin protein and was able to improve polyneuropathy and quality of life following 18 months of treatment in patients with hereditary transthyretin-mediated (hATTR) amyloidosis. In this 24-month Phase II openlabel extension study, we evaluated the effects of patisiran treatment (0.3 mg/kg intravenously every 3 weeks) on safety, serum transthyretin levels, and clinical parameters. Efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…The phase 3 placebo-controlled APOLLO study and the phase 2 open-label extension (OLE) study demonstrated that patisiran achieved robust, rapid, and sustained reduction of serum TTR levels from baseline in patients with ATTRv amyloidosis with polyneuropathy. 6,14 In the 18-month APOLLO study, patients treated with patisiran 0•3 milligrams/kilogram (mg/kg) intravenous (IV) infusion every 3 weeks (q3w) compared with placebo improved in autonomic, sensory, and motor neuropathy as measured by the primary endpoint modified Neuropathy Impairment Score +7 (mNIS+7) as well as across all secondary endpoints including QOL, motor strength, disability, gait speed, nutritional status, 6,15 and exploratory cardiac structure/function endpoints in the pre-specified cardiac sub-population. 16 Patisiran also improved endpoints related to polyneuropathy and QOL, such as mNIS+7 and Norfolk QOL-Diabetic Neuropathy questionnaire (Norfolk QOL-DN), at 18 months compared with baseline in the majority (56% and 51%, respectively) of patients, suggesting reversal of the polyneuropathy of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase 3 placebo-controlled APOLLO study and the phase 2 open-label extension (OLE) study demonstrated that patisiran achieved robust, rapid, and sustained reduction of serum TTR levels from baseline in patients with ATTRv amyloidosis with polyneuropathy. 6,14 In the 18-month APOLLO study, patients treated with patisiran 0•3 milligrams/kilogram (mg/kg) intravenous (IV) infusion every 3 weeks (q3w) compared with placebo improved in autonomic, sensory, and motor neuropathy as measured by the primary endpoint modified Neuropathy Impairment Score +7 (mNIS+7) as well as across all secondary endpoints including QOL, motor strength, disability, gait speed, nutritional status, 6,15 and exploratory cardiac structure/function endpoints in the pre-specified cardiac sub-population. 16 Patisiran also improved endpoints related to polyneuropathy and QOL, such as mNIS+7 and Norfolk QOL-Diabetic Neuropathy questionnaire (Norfolk QOL-DN), at 18 months compared with baseline in the majority (56% and 51%, respectively) of patients, suggesting reversal of the polyneuropathy of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…6 The primary objective of the 24-month phase 2 OLE was to evaluate the safety and tolerability of patisiran, and the study demonstrated both safety and secondary efficacy results consistent with those reported in APOLLO. 14 Eligible patients who completed APOLLO (patisiran or placebo arm) or the phase 2 OLE were able to enrol into the Global OLE which aims to assess the long-term efficacy and safety of patisiran in patients with ATTRv amyloidosis with polyneuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…The disease-stabilizing effect of patisiran was shown to be maintained in an open-label extension phase over 24 months with overall acceptable safety profile. 61 …”
Section: New Therapeutic Options For Unusual Pain Disordersmentioning
confidence: 99%
“…The disease-stabilizing effect of patisiran was shown to be maintained in an open-label extension phase over 24 months with overall acceptable safety profile. 61 Inotersen is a single-strained antisense oligonucleotide, which is complementary to the TTR mRNA. Inotersen binds to the mRNA, this mRNA/DNA heteroduplex is then cleaved by the nuclear ribonuclease H1 (RNase H1) leading to reduced TTR protein levels.…”
mentioning
confidence: 99%
“…More recently, a 24-month, phase 2, open-label extension study, conducted on 27 patients, confirmed the good tolerability and showed an improvement in the modified Neuropathy Impairment Score plus 7 (mNIS+7) of nearly 7 points in 24 months. Motor and autonomic function, as well as quality of life, remained stable, whereas an improvement in nerve-fiber density was documented by skin biopsies [ 61 ].…”
Section: Ttr Mrna Silencersmentioning
confidence: 99%